Teachers Perceptions of Essential Mathematics Concepts in Teacher Education Mathematics Courses - Mosothwane, Modise (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
This study investigates pre-service teachers perceptions of essential components of mathematics education courses offered in primary colleges of education in Botswana. Data for this study were obtained from 11 3rd year student teachers who enrolled in mathematics education courses. The student teachers responded to structured interview protocol questions designed for the study. The analysis of data was framed in qualitative tradition using excerpts taken from student teachers responses .The results of the study suggest that student teachers perceived history of mathematics, modelling, contemporary issues in mathematics education, beliefs and attitudes, mathematics and culture as non- essential parts of mathematics education. The results of the study also suggest that mathematics education courses offered by primary colleges of education do not prepare pre-service teachers for degree courses that would be taken at the university level. Implications for teacher education program are discussed in the light of the findings.